Correlation Between Physicomechanical and Swelling Properties of Weakly Basic Copolymer Hydrogels Based on (Meth)acrylate Polycations as New Smart Materials. Issue 22 (21st October 2015) - Celik, Tayyibe; Orakdogen, Nermin
Abstract : 2‐Hydroxyethyl methacrylate (HEMA) is incorporated to N, N ‐dimethylaminoethyl methacrylate (DMAEMA) fabricating a series of stimuli‐responsive copolymer hydrogels by free radical copolymerization. The increasing comonomer content via adding more HEMA results in a higher network density and, therefore, a lower equilibrium swelling ratio. The uniaxial compressive testing results showed that increasing HEMA in the feed improved the mechanical strength of P(DMAEMA‐co‐HEMA) hydrogels. As HEMA increased, the elastic modulus as well as the effective crosslinked chain density increased. The work strives to provide method to tune mechanical and physical properties for weakly basic copolymer hydrogels based on (meth)acrylate polycations, which is hopefully to guide the design of hydrogels with desirable properties. Abstract : The physico‐mechanical and swelling properties of poly( N, N ‐dimethylaminoethyl methacrylate‐co‐2‐hydroxyethyl methacrylate) hydrogels are investigated to trigger the conformation transition in polymer matrix to control their temperature‐sensitivity. The copolymer hydrogels exhibit strong thermosensitivity owing to the strengthening of the hydrophobic interactions with increasing the temperature.